2012
DOI: 10.1159/000336459
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of the Mole Vole Sibling Species <i>Ellobius tancrei</i> and <i>E. talpinus</i> (Cricetidae, Rodentia) through Chromosome Painting and Examination of Synaptonemal Complex Structures in Hybrids

Abstract: A comparative genomic analysis was carried out in the mole vole sibling species Ellobius tancrei and E. talpinus. Performing fluorescent in situ hybridisation (Zoo-FISH) using chromosome paints from the field vole Microtus agrestis showed no differences in the allocation of syntenic groups in the karyotypes of these sibling species. The only difference between their karyotypes was the position of the centromere in one pair of chromosomes, which is assumed to be the result of an inversion. To verify this hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 47 publications
4
43
0
1
Order By: Relevance
“…It is important that neither differences for male and female chromosomal sets, nor the signal for the Y chromosome probes were revealed. The same results were obtained for species with two X chromosomes in males and females of Е. talpinus and E. tancrei [38]. These results proved the total loss of a Y chromosome, but chromosome painting has a restriction because a fluorescent signal might be unrecognizable in the case of a small fragment, whereas the screening for specific genes is more precise.…”
Section: Ellobius Species and Their Sex Chromosomes Varietysupporting
confidence: 75%
See 1 more Smart Citation
“…It is important that neither differences for male and female chromosomal sets, nor the signal for the Y chromosome probes were revealed. The same results were obtained for species with two X chromosomes in males and females of Е. talpinus and E. tancrei [38]. These results proved the total loss of a Y chromosome, but chromosome painting has a restriction because a fluorescent signal might be unrecognizable in the case of a small fragment, whereas the screening for specific genes is more precise.…”
Section: Ellobius Species and Their Sex Chromosomes Varietysupporting
confidence: 75%
“…50% of newborns are males, and 50% are females. The structures of autosomes and sex chromosomes were studied by chromosome painting of 4 species lacking Y chromosomes; the X chromosome is typical for rodents, and no parts of the Y chromosome were revealed [37,38]. To date, only E. fuscocapillus was not studied by molecular cytogenetic methods.…”
Section: Ellobius Species and Their Sex Chromosomes Varietymentioning
confidence: 99%
“…Mus, Sorex, Ellobius species, and some others exhibit changes in diploid numbers, along with stable fundamental numbers due to whole branch fusions [45][46][47][48]. Recently, using chromosome painting, we described karyotype structures in three cryptic Ellobius species, E. talpinus, E. tancrei, and E. alaicus; we demonstrated a homology of re-arranged chromosomes, and showed the existence of XX sex chromosomes in males and females [49][50][51]. We hypothesized that a neocentromere origin in one pair of chromosomes was an initial disturbance event for the E. tancrei (2n = 54-30) genome, in contrast to stable E. talpinus (2n = 54) [49,52].…”
Section: Introductionmentioning
confidence: 81%
“…Recently, using chromosome painting, we described karyotype structures in three cryptic Ellobius species, E. talpinus, E. tancrei, and E. alaicus; we demonstrated a homology of re-arranged chromosomes, and showed the existence of XX sex chromosomes in males and females [49][50][51]. We hypothesized that a neocentromere origin in one pair of chromosomes was an initial disturbance event for the E. tancrei (2n = 54-30) genome, in contrast to stable E. talpinus (2n = 54) [49,52]. E. alaicus is very close to E. tancrei, a translocation Rb(2.11) emerged in both species; other Rbs are species-specific ones.…”
Section: Introductionmentioning
confidence: 91%
“…It is unclear what could have destabilized the sex chromosomes in E. lutescens , E. tancrei and E. talpinus . F1 hybrids have been identified between E. talpinus and E. tancrei that are sterile, implicating the emergence of reproductive barriers (Bakloushinskaya et al., ; Table ). Fluorescence in situ hybridization revealed that some mammalian Y‐derived genes known to be essential for male fertility have moved to the X chromosome in these two species (Mulugeta et al., ).…”
Section: The Mammalian Sex Determination Switch and The Emergence Of mentioning
confidence: 99%